Effects of early phase 1 cardiac rehabilitation on cardiac function evaluated by impedance cardiography in patients with coronary heart disease and acute heart failure - Wang, Yishu; Xiao, Yanchao; Tang, Jianjun; Liu, Yutao; Li, Hui; Peng, Zengjin; Xu, Danyan; Shen, Li (Frontiers in Cardiovascular Medicine, 2022)
Purpose The purpose of the study was to access the impact of phase 1 cardiac rehabilitation (CR) on cardiac function and hemodynamic changes in patients with coronary heart disease (CHD) and acute heart failure (AHF). Materials and methods A total of 98 patients with CHD and AHF were recruited and randomized into two groups. Control group received standard pharmacotherapy and CR group received standard pharmacotherapy combined phase 1 CR. NT-proBNP and hemodynamic parameters measured by impedance cardiography (ICG) were estimated at baseline and at the end of treatment period. Results Phase 1 CR combined routine medical treatment could lower NT-proBNP levels. The percentage of high-risk patients was significantly decreased in CR group, although the post-treatment NT-proBNP level between control group and CR group showed no significant differences. Similarly, most hemodynamic parameters improved in the CR group, but not in the control group, suggesting that phase 1 CR in combination with the standard pharmacotherapy improved hemodynamic characteristics by elevating cardiac output, ameliorating preload, improving systolic and diastolic function, and relieving afterload, although the post-treatment hemodynamic parameters showed no statistically significant differences between the control group and the CR group. Conclusion Phase 1 CR combined routine medication can improve cardiac function and hemodynamic characteristics in patients with CHD and AHF. Thus, recommendation of phase 1 CR to stable patients is necessary.